Fosb gene products contribute to excitotoxic microglial activation by regulating the expression of complement C5a receptors in microglia. Issue 8 (18th June 2014) - Nomaru, Hiroko; Sakumi, Kunihiko; Katogi, Atsuhisa; Ohnishi, Yoshinori N.; Kajitani, Kosuke; Tsuchimoto, Daisuke; Nestler, Eric J.; Nakabeppu, Yusaku
Abstract : The Fosb gene encodes subunits of the activator protein‐1 transcription factor complex. Two mature mRNAs, Fosb and Δ Fosb, encoding full‐length FOSB and ΔFOSB proteins respectively, are formed by alternative splicing of Fosb mRNA. Fosb products are expressed in several brain regions. Moreover, Fosb‐ null mice exhibit depressive‐like behaviors and adult‐onset spontaneous epilepsy, demonstrating important roles in neurological and psychiatric disorders. Study of Fosb products has focused almost exclusively on neurons; their function in glial cells remains to be explored. In this study, we found that microglia express equivalent levels of Fosb and Δ Fosb mRNAs to hippocampal neurons and, using microarray analysis, we identified six microglial genes whose expression is dependent on Fosb products. Of these genes, we focused on C5ar1 and C5ar2, which encode receptors for complement C5a. In isolated Fosb ‐null microglia, chemotactic responsiveness toward the truncated form of C5a was significantly lower than that in wild‐type cells. Fosb‐ null mice were significantly resistant to kainate‐induced seizures compared with wild‐type mice. C5ar1 mRNA levels and C5aR1 immunoreactivity were increased in wild‐type hippocampus 24 hours after kainate administration; however, such induction was significantly reduced in Fosb ‐null hippocampus. Furthermore, microglial activation after kainate administration was significantly diminished in Fosb ‐null hippocampus, as shown by significant reductions in CD68 immunoreactivity, morphological change and reduced levels of Il6 and Tnf mRNAs, although no change in the number of Iba‐1‐positive cells was observed. These findings demonstrate that, under excitotoxicity, Fosb products contribute to a neuroinflammatory response in the hippocampus through regulation of microglial C5ar1 and C5ar2 expression. GLIA 2014;62:1284–1298 Main Points: Transcription factor Fosb gene products regulate C5ar1 and C5ar2 gene expression in microglia. In the neurodegenerative state, microglial activation was attenuated in Fosb ‐null microglia with decreased expression of C5aR1.